2006
DOI: 10.1590/s0104-11692006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Patient feelings during the preoperative period for cardiac surgery

Abstract: This qualitative study aimed to identify the feelings patients presented when confronted with the news about the need to undergo cardiac surgery and, later, during the preoperative period. Twenty male patients were interviewed. The case study methodology was adopted and the analysis process resulted in two theme categories: Feelings of apprehension (fear, worry, anxiety, suspicion and jittery) and Positive and hopeful feelings. We observed that, although both categories were present at the two moments, over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
(21 reference statements)
1
10
0
11
Order By: Relevance
“…Em relação ao tipo de cirurgia cardíaca e ao sexo dos pacientes, outros estudos corroboram com os resultados encontrados, em que os pacientes do sexo masculino são os que mais se submetem a cirurgia cardíaca e dentre estas cirurgias, as mais freqüentes são as doenças valvares e revascularização do miocárdio (13)(14)(15) . Quanto ao grau de instrução, observou-se que a maioria dos pacientes tinham o primeiro grau incompleto, mesmo resultado encontrado em outro estudo (3) . Em relação à influência destas variáveis na ansiedade dos pacientes, observou-se que nenhuma se correlacionou com os sintomas ansiosos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em relação ao tipo de cirurgia cardíaca e ao sexo dos pacientes, outros estudos corroboram com os resultados encontrados, em que os pacientes do sexo masculino são os que mais se submetem a cirurgia cardíaca e dentre estas cirurgias, as mais freqüentes são as doenças valvares e revascularização do miocárdio (13)(14)(15) . Quanto ao grau de instrução, observou-se que a maioria dos pacientes tinham o primeiro grau incompleto, mesmo resultado encontrado em outro estudo (3) . Em relação à influência destas variáveis na ansiedade dos pacientes, observou-se que nenhuma se correlacionou com os sintomas ansiosos.…”
Section: Discussionunclassified
“…A perspectiva de se submeter à cirurgia cardíaca pode ser causadora de diversas manifestações fisiológicas e psicológicas, principalmente medo e ansiedade (3) . Estas manifestações tornam-se mais intensas, principalmente antes do procedimento, uma vez que o medo do desconhecido causa insegurança e ansiedade.…”
Section: Introductionunclassified
“…This finding is consistent with those of Vargus et al . (), who indicated that knowing the precise moment of being scheduled for heart surgery induces anxiety. Heart surgery wears on patients emotionally, because of the threats it poses to life and daily functioning; this anxiety might be caused by the fact that the heart has cultural meaning as being responsible for emotions and controlling life.…”
Section: Discussionmentioning
confidence: 99%
“…It can directly influence the postoperative recovery, therefore, it is relevant to approach and identify patients' feelings from the preoperative, guiding them and clarifying questions concerning the different periods, which tends to reduce anxiety and facilitate the recovery (22) . Consequently, the nursing care needs to approach patients integrally during the postoperative period, covering their post-surgery complications and offering emotional support to patients and their families.…”
Section: Discussionmentioning
confidence: 99%